Analisis Perbaikan Kurikulum SMK Berbasis Pada Framework Cobit 2019 - Rosnanto, Imam; Fatonah, Nenden Siti; Firmansyah, Gerry; Tjahjono, Budi; Akbar , Habibullah (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to analyze improvements to the Vocational High School (SMK) curriculum based on the COBIT 2019 framework as a standard for IT governance. Amid the rapid development of Industry 4.0 and digital transformation, the SMK curriculum must be adaptive and relevant to equip students with competencies aligned with workforce demands. The research uses a qualitative approach involving literature review, interviews, and an IT governance audit in vocational education. The analysis focuses on the Governance and Management domains of COBIT 2019 and their relation to the current SMK curriculum structure. The audit and analysis reveal gaps in risk management, information security, and curriculum implementation compared to ideal IT governance principles. Recommendations include strengthening curriculum planning, integrating digital competencies, and applying outcome-based performance measurement. This study is expected to contribute to improving vocational education quality through the effective and sustainable application of IT governance principles.